PARTICIPANTS' REACTIONS TO THE IMPLEMENTATION OF MOOC IN THE LATSAR CPNS TRAINING IN THE MINISTRY OF LAW AND HUMAN RIGHTS - Budianto, Dona Indra Wira; Ramdhani, Nungki Awalya (Universitas Pendidikan Indonesia, 2024)
Massive Open Online Courses (MOOCs) is a form of online learning that is developing and getting a lot of attention in digital learning. This research is a quantitative study using a questionnaire to the participants of the LATSAR CPNS (basic training for civil servants candidates) at the Ministry of Law and Human Rights Indonesia with a sampling of 296 people. The researcher asked the participants' reactions to the training implementation and their perception of learning acquired. From this study, it can be concluded that the training participants gave positive responses to the MOOC LATSAR CPNS in the Ministry of Law and Human Rights, especially towards learning objectives, training materials, learning processes, assessment systems and ease of accessing portals. In the evaluation of learning outcomes, participants also felt that their knowledge was increased if they compared their knowledge before and after attending the MOOC training. This study describes a good opportunity for the implementation of the MOOC learning method for the competency development for civil servants widely, both within the Ministry of Law and Human Rights and other government institutions.